THREATS TO BIODIVERSITY AND THE ROLE OF CONSERVATION BIOLOGY FOR FUTURE SUSTAINABILITY: A REVIEW - Ejeta, Adugna Gindaba; Bekele, Getachew (International Journal of Research -GRANTHAALAYAH, 2017)
More than half the habitable surface of the Earth has already been significantly altered by human activity. Therefore, this review was conducted to show threats to biodiversity and the role of Conservation Biology for future sustainability. Scientists suggested that this planet’s species are on the verge of mass extinction while our knowledge of diversity and variability of plants, animals, microorganisms and the ecosystem in which they occurs incomplete. Humans’ pressure affect biodiversity by: (1) over harvesting of resources, (2) Habitat destruction, conversion, fragmentation of habitats i.e. degradation and loss, (3) introduction of exotic or invasive organisms and diseases i.e. non- native invasive species (4) Pollution of soil, water and atmosphere, and (5) global environmental change. Conservation Biology is a new stage in the application of science to conservation problems, addresses the biology of species, communities, and ecosystems that are perturbed, either directly or indirectly, by human activities. In addition, it is a multi-disciplinary field that provides 3 overriding principles to guide conservation: First, evolution is the basis for understanding all of biology, and should be a central focus of conservation action. Second, ecological systems are dynamic and non-equilibrial, and therefore change must be a part of conservation. Finally, humans are a part of the natural world and must be included in conservation concerns.